Keefektifan Pembelajaran Menulis Surat Pribadi Untuk Kepentingan Resmi Menggunakan Model Pembelajaran M4 (Make A Match-Mind Map) Dengan Media Gambar Pada Siswa Kelas Vii Smp - Nurul Fajriyah; Wagiran Wagiran (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract : This study aims to determine the effectiveness of writing personal letter of official purposes study using the M4 (Make a Match-Mind Map) learning model. This research uses quasi experimental method with nonequivalent control group design. The population of this research is class VII of SMP Negeri 4 Magelang with sample of class VII E. The result of this research is M4 learning model effective used in writing personal letter for official purposes study is evidenced by increasing average of pretest and posttest that reaches 19.62 and the significance value of t test result is 0,000 < 0,05 which means there is a significant difference between the pretest and posttest of M4 learning model. In addition, as many as 18 students or 85.72% in category of very good or effective in writing a personal letter for official purposes. Keywords : model pembelajaran M4, surat pribadi untuk kepentingan resmi